LEGAL STRATEGIES IN INCREASING FOREIGN DIRECT INVESTMENT IN INDONESIA - Erwin Erwin; Noorsidi Aizuddin Mat Noor; Muhammad Bagus Adi Wicaksono (INJOSEDU: International Journal of Social and Education, 2025)
Increasing Foreign Direct Investment (FDI) is one of the top priorities for governments in many countries due to its crucial role in driving economic growth and development. In order to achieve this goal, effective legal strategies play an important role in creating a conducive investment environment. The research method used in this study is the literature research method. The results show that successful IALs are those that have successfully simplified their licensing procedures and adopted transparency in the regulatory process. In addition, the provision of strong legal protection of investor rights, including through intellectual property enforcement and fair and efficient dispute resolution mechanisms, has also been shown to increase foreign investor confidence. Therefore, an effective legal strategy in enhancing IAL should include a blend of process simplification, legal certainty, investor protection, and social responsibility to create an attractive investment environment for foreign investors.